2016
DOI: 10.1080/23750472.2016.1255563
|View full text |Cite|
|
Sign up to set email alerts
|

Too busy or too far away? The importance of subjective constraints and spatial factors for sports frequency

Abstract: Previous studies on the association between the availability of sports facilities and sports participation have neglected the influence of subjective constraints that individuals experience with regard to sports participation. This paper investigates to what extent constraints experienced by sports participants are associated with their spatial circumstances and whether these subjective constraints or objective spatial circumstances have a greater impact on sports frequency. Based on a survey among 776 adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…This is clearly an issue in sport participation, as lack of time is by far the most mentioned reason for not practising sport (European Commission, 2014). The main constraints reported for sport participation relate to work or study, social commitments, and family obligations (Deelen, Ettema, & Dijst, 2016). Not only is time scarce, but time devoted to one activity often must be traded off against time required for other pursuits.…”
Section: The Effects Of Major Life Events: a Resource Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…This is clearly an issue in sport participation, as lack of time is by far the most mentioned reason for not practising sport (European Commission, 2014). The main constraints reported for sport participation relate to work or study, social commitments, and family obligations (Deelen, Ettema, & Dijst, 2016). Not only is time scarce, but time devoted to one activity often must be traded off against time required for other pursuits.…”
Section: The Effects Of Major Life Events: a Resource Approachmentioning
confidence: 99%
“…Major life events that accompany the transition to adulthoodlike leaving full-time education and beginning work, entering an intimate relationship, formalising a relationship through cohabitation or marriage, and becoming a parentimpose restrictions on time to practise sport (Deelen et al, 2016;Kraaykamp et al, 2009;Ruseski, Humphreys, Hallmann, & Breuer, 2011;Tiessen-Raaphorst, Van den Dool, & Vogels, 2014;Van Houten et al, 2014, 2017. These major events, additionally, bring new roles and social responsibilities, like maintaining a professional and family network, providing for a partner, and taking care of a child, which are likely to be of greater importance than sport-related roles and responsibilities.…”
Section: The Effects Of Major Life Events: Expectationsmentioning
confidence: 99%
“…For instance, a previous study found that runners not only use the public space in their neighbourhood, however, they also go outside the neighbourhood and out of town [ 24 ]. Moreover, our data showed that sports participants using sports clubs or private sports facilities on average travelled 3082 m (SD = 3.843 m) to their sports activities (see also [ 16 ] based on the same data), and those who use the public space for sports such as running will probably use an even wider area around their homes.…”
Section: Methodsmentioning
confidence: 86%
“…That natural environmental characteristics (i.e., green and blue space) are related to sports participation is in line with previous research that showed that attractive and liveable environments stimulate and invite people to exercise or participate in sports [ 31 , 32 ]. Moreover, such environments are associated with less experienced constraints to participating in sports more frequently [ 16 ]. The strong effect of green, and particularly blue space, on sports participation in all types of locations might be related to different types of sports that different natural areas are suitable for.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation